OPTIMALISASI PENGELOLAAN KELAS OLEH GURU TAMAN PENDIDIKAN AL-QUR’AN ( TPQ ) MUSHALLA MUKHLISIN DI NAGARI KUBU TAPAN KECAMATAN RANAH AMPEK HULU KABUPATEN PESISIR SELATAN - Andika Saputra; Salmi Wati; Arman Husni; Charles (KOLONI, 2022)
This research is motivated by problems in classroom management, namely, in the learning activities of grades 1 to grade 6 are united in one class, teachers pay less attention to students in explaining learning, and teachers do not apply sanctions to students who violate the rules. This research uses qualitative research, using qualitative descriptive research methods. Sources of data obtained through informants include key informants, namely TPQ Mushalla Mukhlisin teacher and supporting informants, namely TPQ Mushalla Mukhlisin students. In collecting data, using observation and interviews. Data analysis uses data reduction, data presentation, and data verification. From the results of this study, in optimizing classroom management at TPQ Mushalla Mukhlisin the teacher has implemented some components of class management skills, the first component relating to the creation and maintenance of optimal learning conditions that have been implemented is to provide clear instructions and reprimand, meanwhile that have not been applied are responsiveness, sharing attention, focusing group attention, and providing reinforcement. The second component of Skills related to controlling optimal learning conditions that have been applied is finding and solving behavior that causes problems, while what has not been applied is modifying behavior and group management. In an effort to optimize classroom management, teachers face several obstacles, including teachers who have not mastered classroom management skills, students are difficult to manage and limited facilities in teaching. Keyword: TPQ Class Management Optimization